A comprehensive approach of community environmental issues in local junior high school curriculum - Núñez Pardo , M. Sc. Pedro Juan (Transformación, 2024)
The paper describes the findings of a research carried out at “Silverio Blanco Núñez” Junior High School aimed at including environmental community problems in the curriculum. Theoretical methods were used to construct a rationale, surveys interviews and observation to characterize the object of study and controlled experiment to evaluate the impact of the methodology for integrating environmental community problems to the education system. The methodology is structured into four comprehensive axes that favor students, teacher and neighbors’ enrollment in curricular and extra-curricular activities contributing to prevention, mitigation and solution on the basis of causes and consequences knowledge. Key words: environmental issues, environmental education, environment, community.